(untitled) (Altre Modernità, 2015)
Renée Ferrer, Racconti dall’isola senza mare (Salerno-Milano, Oèdipus, 2014, 120 pp. ISBN 978-88-7341-191-8, traduzione di Maria Gabriella Dionisi) di Ilaria Magnani